Pentoxifylline: A promising solution for reducing proteinuria in type 2 diabetes patients - Karmani, Jais Kumar; Ali, Mohammad; Yasmin, Rifat; Shah, Syed Asim Ali; Baig, Wajahat Sultan; Haq, Muhammad Farhan Ul (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the effects of pentoxifylline on reducing proteinuria in diabetic patients. Methods: A randomized placebo-controlled trial was conducted at the Nephrology department of Akbar Niazi Teaching Hospital, Islamabad and the Medicine department of Pakistan Ordnance Factory (POF) Hospital, Wah Cantt, Pakistan from January to June 2024. A total of 170 patients with type 2 diabetes on ACE inhibitors and ARBs but still having proteinuria over 500 mg/24 hours were enrolled in the study. 85 patients and placebo-treated volunteers formed the control group. Patients received 400 milligrams of oral pentoxifylline thrice daily. Proteinuria was measured for 24 hours at the onset of the experiment and during the initial quarter and half a year after pentoxifylline administration. In the other group, 85 healthy participants received a placebo. Results: The mean age of the patients was 59.2±10.2 years (ranging; from 18 to 70 years), with 56.5% (n=96) male and 43.5% (n=74) female. Patients who consumed oral pentoxifylline decreased proteinuria significantly (p ≤ 0.05). Proteinuria decreased over the initial three months were significant (p ≤ 0.05). Conclusion: According to trial data, pentoxifylline three times a day reduces proteinuria and prevents renal failure. The dosage does not affect the kidneys.